Life-threatening acute subdural haematoma after combined spinal-epidural anaesthesia in labour - Bakar,Bulent (2015)
ABSTRACTBACKGROUND AND OBJECTIVES: Only few reports in literature have pointed out to the possibility of a cranial subdural haematoma formation associated with dural puncture during spinal or epidural analgesia. We herein describe such a rare case who was diagnosed to have acute subdural haematoma after combined spinal-epidural anaesthesia used in labour.CASE REPORT: A 34-year-old, primigravid women with a gestation of 38 weeks underwent caesarean section under combined spinal-epidural anaesthesia and gave birth to a healthy boy. Thirty-two hours after delivery, her moderate headache progressed to a severe headache associated with nausea and vomiting and later was more complicated with a generalized tonic-clonic seizure and ensuing lethargy. Computed tomography of the brain demonstrated a right-sided fronto-temporo-parietal acute subdural haematoma with diffuse cerebral oedema. She underwent urgent FTP craniotomy and evacuation of the haematoma. Early postoperative cranial computed tomography showed a clean operative site. Eight days after subdural haematoma surgery, she became lethargic again, and this time cranial computed tomography disclosed an extradural haematoma under the bone flap for which she had to undergo surgery again. Two days later, she was discharged home with Karnofsky performance score of 90/100. At follow-up exam, she was neurologically intact and her cranial computed tomography and magnetic resonance were normal.CONCLUSIONS: As conclusion, with the use of this combined spinal-epidural anaesthesia, it should be kept in mind that headache does not always mean low pressure headache associated with spinal anaesthesia and that a catastrophic complication of subdural haematoma may also occur.